Bibliometric analysis of highly cited papers on oral mucosal lesions in COVID-19: Trends and impact in medical literature - Namrata Sengupta; Gargi Sarode; Rahul Anand; Sachin C. Sarode (Journal of Oral Biology and Craniofacial Research)
Objective: Bibliometric analysis of highly cited papers facilitates researchers in formulating strategic research possibilities and addressing gaps in specific domains. In this context, a bibliometric analysis was conducted to identify published papers on “oral mucosal lesions in COVID-19” within medical literature. Methods: A comprehensive search was performed in the Scopus database in July 2023. Relevant articles were retrieved, reviewed, and data for the bibliometric analysis was recorded. Network visualization of authors, countries, and keywords was generated using VOSviewer software. Results: The analyzed articles were published over the last three years, from 2020 to 2023, with the highest output observed in 2021. The citation count for individual papers ranged from 1 to 340, with a mean of 22.325 ± 58.93 citations. A total of 37 journals were involved in publishing papers on this topic, and five authors each contributed three papers. Notably, Brazil made the highest number of contributions with eight papers. Among the 40 papers, 19 were review papers and 16 were articles discussing various aspects of oral mucosal lesions in COVID-19 patients. Additionally, six papers were identified as systematic reviews, designated with a high level of evidence. Conclusions: This study presents a comprehensive bibliometric analysis of papers published on “oral mucosal lesions in COVID-19.” The findings will assist researchers in identifying impactful papers, understanding the prevailing research trends, and guiding future research directions in this domain. The insights gained from this analysis can contribute significantly to advancing knowledge and improving patient care in this critical area of study.